1993
DOI: 10.1111/j.1365-3040.1996.tb02065.x
|View full text |Cite
|
Sign up to set email alerts
|

Is wall‐bound calcium redistributed during the gravireaction of stems and coleoptiles?

Abstract: We have tested the hypothesis that wall-bound calcium is redistributed from the lower to the upper sides of horizontal stems and coleoptiles during the reaction phase of gravicurvature. We used atomic absorption spectrometry to measure wall-bound calcium in the epidermal and internal layers of sunflower {Helianthus annuus L.) hypocotyls and pea (Pisum sativum L.) epicotyls, and total calcium in maize (Zea mays L.) coleoptiles at the time of maximal gravireaction. In every case, we found that there was no measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Firstly, it is thought that gravitropic signalling initiates a redistribution of wall-bound calcium (Roux and Serlin 1987 and references therein). Calcium accumulations have been detected on the slower-growing side of both shoots and roots (Roux and Slocum 1982;Lee et al 1983a), although this may not always be observed (Bagshaw and Cleland 1994). Since exogenously applied Ca 2+ has frequently been reported to inhibit growth, and chelators to promote growth, these observations provide a simple means of curvature control, a point elegantly demonstrated by Lee et al (1983b).…”
Section: Introductionmentioning
confidence: 94%
“…Firstly, it is thought that gravitropic signalling initiates a redistribution of wall-bound calcium (Roux and Serlin 1987 and references therein). Calcium accumulations have been detected on the slower-growing side of both shoots and roots (Roux and Slocum 1982;Lee et al 1983a), although this may not always be observed (Bagshaw and Cleland 1994). Since exogenously applied Ca 2+ has frequently been reported to inhibit growth, and chelators to promote growth, these observations provide a simple means of curvature control, a point elegantly demonstrated by Lee et al (1983b).…”
Section: Introductionmentioning
confidence: 94%
“…Displacement of the EGTA with Ca 2+ solution was followed by gravitropism. The question of a possible redistribution of Ca 2+ in the cell walls of shoots during a gravitropic response was investigated by Bagshaw and Cleland (1993a) by measuring the Ca 2+ concentration in cell walls of epidermal and cortical cells of gravitystimulated Pisum epicotyls, Helianthus hypocotyls and Zea coleoptiles. The authors found no evidence for apoplasmic movement of Ca 2+ due to gravity.…”
Section: Epicotyls Hypocotyls and Coleoptilesmentioning
confidence: 99%
“…These data were then used to quantify the spatiotemporal behavior of the gravitropic response. In some studies of gravitropism, changes in axis shape have been quantified by the change in stem tip angle (Bagshaw and Cleland, 1993;Perbal and DrissEcole, 1994). As stated by Firn and Digby (1980), this can lead to artifacts in the interpretation of axis shape changes because the tip angle is dependent on an integrated value, i.e.…”
mentioning
confidence: 99%